2019
DOI: 10.2174/1385272822666180803123137
|View full text |Cite
|
Sign up to set email alerts
|

Organodiselenides: Organic Catalysis and Drug Design Learning from Glutathione Peroxidase

Abstract: Organodiselenides are an important class of compounds characterized by the presence of two adjacent covalently bonded selenium nuclei. Among them, diaryldiselenides and their parent compound diphenyl diselenide attract continuing interest in chemistry as well as in close disciplines like medicinal chemistry, pharmacology and biochemistry. A search in SCOPUS database has revealed that in the last three years 105 papers have been published on the archetypal diphenyl diselenide and its use in organic catalysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 201 publications
(206 reference statements)
0
34
0
Order By: Relevance
“…Computational methodologies are nowadays largely employed to rationalize chemical and biochemical phenomena. Particularly, accurate mechanistic studies on the control of oxidative stress by endogenous defenses, including enzymes such as glutathione peroxidase [30][31][32], and molecular drugs that act as mimics of these enzymes [33][34][35][36][37] or as radical scavengers [38] have been reported by some of us. In this work, we investigate in silico the antioxidant activity of fluoxetine via HAT (hydrogen atom transfer) and RAF (radical adduct formation) mechanisms.…”
Section: Aim Of This Workmentioning
confidence: 99%
“…Computational methodologies are nowadays largely employed to rationalize chemical and biochemical phenomena. Particularly, accurate mechanistic studies on the control of oxidative stress by endogenous defenses, including enzymes such as glutathione peroxidase [30][31][32], and molecular drugs that act as mimics of these enzymes [33][34][35][36][37] or as radical scavengers [38] have been reported by some of us. In this work, we investigate in silico the antioxidant activity of fluoxetine via HAT (hydrogen atom transfer) and RAF (radical adduct formation) mechanisms.…”
Section: Aim Of This Workmentioning
confidence: 99%
“…Recently, the chalcogen bond has received much attention due to the promising features making it amenable to application in many fields such as catalysis, ion transport and material and drug design. [22][23][24][25][26][27][28] In addition to that, a very recent survey of the PDB database showed that many protein-ligand complexes, in which the ligand contains a chalcogen atom, adopt structures that allow the formation of chalcogen bonds. 29 In this work, we focus our attention on a particular kind of bond acceptors, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the radical scavenging activity via HAT (Hydrogen Atom Transfer) mechanism, recently reported for uoxetine, 17 selenouoxetine and its derivatives have the capacity of reducing hydroperoxides and H 2 O 2 as GPx mimics. [23][24][25] The biological role of selenium is a long-debated issue since its identication in GPx, an enzyme able to protect cells from oxidative stress by inactivating hydroperoxides. [26][27][28][29][30] As oen happens, nature inspired medicinal chemists and synthetic selenium-based compounds were developed through the years to mimic GPx activity as well as to exert antioxidant activity through other mechanisms, such as metal binding.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30] As oen happens, nature inspired medicinal chemists and synthetic selenium-based compounds were developed through the years to mimic GPx activity as well as to exert antioxidant activity through other mechanisms, such as metal binding. [23][24][25]31 Among GPx mimics, ebselen (2-phenyl-1,2-benzisoselenazol-3(2H)-one) is the most popular since it was employed in clinical trials. 32 Aryl and alkyl selenides, 33,34 together with aryl diselenides, [35][36][37][38] have been prepared and tested in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%